Role of Hydrology in the Design of Soil Sr Water Conservation Structures - Sarkar, T.K. (Journal of Soil and Water Conservation, 2022)
The importance of natural hydrological Processes in the watershed has been pointed out for design of Soil and Water Conservation measures. The would enable to make optimum use of soil and water resources for sustainable development on the watershed.